Edukasi Pemilu 2024 Kepada Pemilih Pemula: "Sosialisasi Pemuda Paham Pemilu" - Suhartini Suhartini; Muhammad Zidane Firmansyah; Zalfa Khalisah Qonitah (Abdimas Universal, 2024)
A General Elections or what we know as Elections. General Elections are held every 5 (five)  years. Elections can be said to be the initial stage of a series of life arrangements in democratic constitutionality. Elections are a form of democracy and the freedom of the people to participate in politics as well as a form of evidence that sovereignty is in the hands of the people. The problem that is often encountered in elections is the lack of understanding and self-awareness of novice voters in the right to vote. The Socialisation of Youth Understanding and Smart Elections carried out by students of the law faculty of Balikpapan University which was held at SMK Negeri 2 Balikpapan, East Kalimantan. This activity is intended to increase understanding, especially young people as novice voters for the upcoming 2024 election so that general elections are held directly, publicly, freely, confidentially, honestly, and fairly. This activity was attended by approximately 50 Students with the presentation of two materials by Lecturers of the Faculty of Law, Balikpapan University and the Koordiv SDMO and the Balikpapan City Bawaslu Training. Not only the presentation of this activity material was held a question and answer session by law faculty students in order to increase understanding of the election.